Designing tests for some motor abilities and predicting the level of performance skill for academic school football players aged (13-14) years (Raparin Journal of Humanities (RJH), 2024)
The study aims to design tests to measure some motor abilities in the study sample, to find standard grades and levels for some tests of motor abilities in the study sample, preparing equations to predict the level of performance skill of soccer players in terms of mobility tests in the research sample. The researcher used the descriptive approach, and the research community was selected from football academy players aged (13-14) years in Raparin. The research sample was selected intentionally, which included (260) players. So as to reach the results, the researcher used a set of statistical programs by using SPSS. It was concluded to find and determine the grades and standard levels modified for the research sample in the motor tests, determining an equation to predict the level of performance skill in terms of motor abilities. It is recommended that the prediction equation can be adopted as indicators through which the components of motor abilities are determined and the possibility of upgrading it according to the time period of the preparation stage to reach the level of competition.